The impact of emotional attachment and culture on the breakup strategies perceived by the abandoned - Retana-Franco, Blanca Estela; Sánchez-Aragón, Rozzana (Acta colombiana de psicología, 2020)
Abstract Considering the importance that has it been given to couple relationships, their breakdown has a negative impact on its members, especially on those who are victims (passive role) of the other's decision. Thus, from the cultural point of view, when a great value is attributed to romantic relationships, in terms of personal and family fulfillment, and this is transmitted to the members of the couple, facilitating the development of beliefs, norms, attitudes and expectations about the love experience, the search and consummation of that love becomes a guideline in people's lives. And if coupled with this, the attachment representing the means by which the biological needs for affection and security are met through the connection with another, it can be devastating to lose the source of such satisfactions. Based on the foregoing, the purpose of this study was to identify the relationship between the historic socio-cultural premises (PHSC, for its Spanish acronym) about romantic mourning and the attachment styles with the breakup strategies perceived by the passive subjects with a positive and negative romantic history. To do this, the study used a non-probabilistic sample of 547 residents of Mexico City who had been left by their partner. After performing some correlation analyzes, results indicated that the PHSC's have greater effects on the perception of negative breakup strategies in people with a positive or negative romantic history. The effects increased when dealing with PHSC's about feelings, mainly in passive members with a negative history and with an anxious attachment style followed by those with avoidant style. For their part, positive PHSCs are associated, but at a low level, with any perceived strategy.